ANALISIS EFISIENSI PEMASARAN TAHU DI KELURAHAN KEKALIK JAYA KOTA MATARAM - WEDASTRA, MADE SUMA (Universitas Mahasaraswati K. Mataram, 2024)
The research carried out in Kekalik Jaya Village, Sekarbela District, Mataram City aims to determine the marketing channels and marketing efficiency of tofu in Kekalik Jaya Village, Sekarbela District, Mataram City. The sample was determined proportionally by Random Side as many as 30 craftsmen, while for retailers the sample was determined as 10 people by snowballing. To analyze marketing efficiency, marketing margin analysis and producer price share are used. Tofu marketing is said to be efficient if: marketing margin is low, producer price share is > 60%. From the research results it can be concluded as follows: 1). There are 2 (two) tofu marketing channels in Kekalik Jaya Village, Mataram City, namely: a). tofu crafters - final consumers, b). Tofu craftsmen – retailers- final consumers. 2). Judging from marketing efficiency, the two marketing channels are efficient because the marketing margin in channel 1 (producer – final consumer) is IDR 0 (0.%) and in channel II the margin is IDR. 150 (17.65%) and the two channels share the price received by producers > 60%.It is recommended to producers when there is little production to sell their production directly to consumers (channel I), because there is no price difference, and 100% of the price share is received by the producer, but when tofu craftsmen produce a lot they should use channel II, meaning other than Selling directly to end consumers also sells to retailers who are customers, because they must also look at the characteristics of tofu which are easily damaged.